Auditoría admistrativa y su incidencia en los procesos de comercialización de la empresa agroservicios comercial Arias, cantón el Empalme, año 2013 - Álava Carbo, Ana Karen (2016)
This research was conducted at the El Empalme Canton Road in Manabi, whose work lasted 90 days., With the overall objective Run a Management Audit help strengthen marketing processes Business Business services Agro-Arias, El Empalme Canton. And the specific objectives Browse administrative functions and its relationship to the sales operation of the Company. Evaluate internal control for identifying strengths and weaknesses administrative - commercial; Determine the effectiveness, efficiency and effectiveness of business activities that contribute to strengthening the processes of marketing and Issue Management Audit report to enable the provision of a corrective action plan for the company. The results were: Analyzing Agro Administrative functions in the service business - commercial Arias was identified that the sales operation goes according to what is stated in the manual functions held by the institution; Assess internal control within Agro Arias service helping you identify the strengths and weaknesses administrative - business through the implementation of the components which were: control environment, control activities, risk assessment, information, communication, monitoring and monitoring, which demonstrated maintain excellent control in the administration of the company, obtaining a confidence level of 86.75% and a risk level of 13.25% thus obtaining a low- risk and low risk audit of the 0.33% considering it as acceptable; Use the Management Audit in commercial activities of the Agro Service Arias measuring the effectiveness, efficiency and effectiveness in order to obtain the strengthening of marketing processes; Issue Management Audit final report of the company Agro Service Arias for you to adopt a plan of action and correct the anomalies found in the company.